EDUKASI PENGATURAN PENYIMPANAN DAN PENGEMASAN PRODUK DAGING POTONG UMKM YBS SUPPLIER & LOGISTIC - Putu Yudy Wijaya; Ni Nyoman Reni Suasih; I Kadek Noppi Adi Jaya (Jurnal Abdi Insani, 2022)
Meat is one of the basic necessities and is a food item that has high nutritional value, but is susceptible to damage due to microbes. Therefore, the packaging of meat products also needs to meet the information standards that consumers must know. MSME YBS Supplier & Logistic is an MSME located in Gianyar Regency, Bali Province and sells meat products. According to the results of initial observations, the MSME managers do not yet have education regarding product storage and packaging arrangements. The purpose of this activity is to provide education about the management and storage and packaging techniques (including logos and packaging labels) of meat products at YBS Supplier & Logistic SMEs. In the early stages of service, counseling and training were carried out on product storage techniques. Furthermore, logos and product packaging labels are made that are designed through a discussion process with MSME managers. The final stage is training related to the storage and packaging of meat products. MSME YBS Supplier & Logistics has received education about meat product storage techniques according to their purpose, namely through refrigeration techniques or freezing techniques. Also explained about tips for announcing meat before storage. YBS Supplier & Logistics SMEs have also received equipment assistance in the form of a freezer and vacuum sealer. Regarding product packaging, a logo has been compiled which is a combination of logogram and logotype. Furthermore, through discussion also design informative product packaging labels. The information presented is in the form of logo, product type, weight, production date, and contacts (including social media and website). Through the service, education, training and assistance have been provided for storage devices, and the preparation of logos and packaging labels has been carried out.